2011
DOI: 10.1093/glycob/cwq220
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping, expression and post-translational modifications of two isoforms of CD33 (CD33M and CD33m) on lymphoid and myeloid human cells

Abstract: We have tested the usefulness of several commercial anti-CD33 monoclonal antibodies (mAb) to determine the expression and localization of the two CD33 isoforms on several hematopoietic cell lines. The expression of the isoform CD33m, a CD33 transmembrane splice variant lacking the ligand-binding V immunoglobulin (Ig)-like domain, was detected by RT-polymerase chain reaction, western blot, confocal microscopy and flow cytometry on the membrane of several human cell types. CD33m was only detected by the anti-CD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 27 publications
7
62
0
Order By: Relevance
“…We used tagged versions of the CD33 proteins to distinguish those from endogenously expressed CD33 in some of these cell lines and to be able to track the CD33 ∆E2 and CD33 ∆E2,E7a variants. While previous studies suggested that one CD33 antibody (clone Him3-4) specifically recognizes the C 2 - set Ig-like domain and could be used to detect CD33 variants that lack exon 2 [9], in our experiments Him3- 4 only recognized CD33 FL and CD33 E7a but not CD33 ∆E2 or CD33 ∆E2,E7a when expressed in virally-transduced ALL cell lines that are devoid of endogenous CD33 (Jurkat, RCH-ACV, REH, or RS4;11: Figure 3) and only recognized CD33 FL but not CD33 ∆E2 when expressed in virally-transduced HEK293T cells (Figure 4). As shown in Figure 5, engineered sublines expressed high amounts of CD33 FL and CD33 E7a in all cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…We used tagged versions of the CD33 proteins to distinguish those from endogenously expressed CD33 in some of these cell lines and to be able to track the CD33 ∆E2 and CD33 ∆E2,E7a variants. While previous studies suggested that one CD33 antibody (clone Him3-4) specifically recognizes the C 2 - set Ig-like domain and could be used to detect CD33 variants that lack exon 2 [9], in our experiments Him3- 4 only recognized CD33 FL and CD33 E7a but not CD33 ∆E2 or CD33 ∆E2,E7a when expressed in virally-transduced ALL cell lines that are devoid of endogenous CD33 (Jurkat, RCH-ACV, REH, or RS4;11: Figure 3) and only recognized CD33 FL but not CD33 ∆E2 when expressed in virally-transduced HEK293T cells (Figure 4). As shown in Figure 5, engineered sublines expressed high amounts of CD33 FL and CD33 E7a in all cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…We also performed CD14 immunostaining by incubation of cells with FITC-conjugated 61D3, and after a washing step, they were stained with PE conjugated MФP9- mAb. The fluorescence intensity was analyzed by flow cytometry, and compared to that displayed by direct staining with the fluorochrome-conjugated 3G8- PE-Cy5 or MФP9-PE mAb on neutrophils or monocytes, respectively [21]. …”
Section: Methodsmentioning
confidence: 99%
“…The expression of siglecs has been demonstrated on various cell types in a restricted pattern. Thus, Siglec-1 is expressed on macrophages, Siglec-2 on B lymphocytes, Siglec-3 on cells of the lymphoid and myeloid cells such as macrophages, monocytes and microglia (Varki and Angata 2006;Perez-Oliva et al 2011) and MAG/Siglec-4 on myelin-forming cells, the Schwann cells and oligodendrocytes (Matani et al 2007). Siglecs are single-pass (type 1) transmembrane proteins with variable numbers (1-16) of Ig-like constant region type 2 (C2-set Ig-like) domains and an amino-terminal Ig-like variable (V-set Ig-like) domain that bears the sialic-acid-binding site (Crocker 2005;Varki and Angata 2006;Crocker et al 2007;Varki 2009).…”
Section: Sgag-binding Receptorsmentioning
confidence: 99%